2016
DOI: 10.1111/ejn.13298
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute tryptophan depletion on central processing of CT‐targeted and discriminatory touch in humans

Abstract: C-tactile afferents (CTs) are slowly conducting nerve fibres, present only in hairy skin. They are optimally activated by slow, gentle stroking touch, such as those experienced during a caress. CT stimulation activates affective processing brain regions, alluding to their role in affective touch perception. We tested a theory that CT-activating touch engages the pro-social functions of serotonin, by determining whether reducing serotonin, through acute tryptophan depletion, diminishes subjective pleasantness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 99 publications
(136 reference statements)
4
23
0
Order By: Relevance
“…OTR knockdown increased the number of perineuronal nets in the S1 (Figs 4I-K), while it decreased the number of perineuronal nets in the lOFC (Fig 4Q). These effects of OTR knockdown may have been driven by serotonin’s potentiation of cortical inhibition 68,78 , with serotonin release associated with decreased activity of the S1 in response to tactile stimulation in both female rats 79,80 and women 68 . Perineuronal nets are generated in response to neural activity 73 , so greater S1 activity and lower lOFC activity could have led to the higher and lower number of perineuronal nets in the S1 and lOFC, respectively (Figs 4I-K, 4Q).…”
Section: Otrs Influence Cortical Serotonin and Perineuronal Netsmentioning
confidence: 99%
“…OTR knockdown increased the number of perineuronal nets in the S1 (Figs 4I-K), while it decreased the number of perineuronal nets in the lOFC (Fig 4Q). These effects of OTR knockdown may have been driven by serotonin’s potentiation of cortical inhibition 68,78 , with serotonin release associated with decreased activity of the S1 in response to tactile stimulation in both female rats 79,80 and women 68 . Perineuronal nets are generated in response to neural activity 73 , so greater S1 activity and lower lOFC activity could have led to the higher and lower number of perineuronal nets in the S1 and lOFC, respectively (Figs 4I-K, 4Q).…”
Section: Otrs Influence Cortical Serotonin and Perineuronal Netsmentioning
confidence: 99%
“…In humans, evidence for the specific rewarding value of CT activating touch comes from a range of fMRI studies which consistently shown that gentle stroking applied to hairy but not palmar skin at CT optimal velocity, reliably produces neural activation in affective and reward related brain regions (Gordon et al, 2013;McGlone et al, 2012;Olausson et al, 2002;Trotter et al, 2016). These areas form key nodes of neural networks with an established role in guiding aspects of social perception, cognition and behaviour (Adolphs, 2003).…”
Section: Are C-tactile Afferents the Sensory Nerves Mediating The Phymentioning
confidence: 99%
“…CT-preferred stimulation activates dorsal posterior insula and orbitofrontal cortex and is related to the pleasurableness of the experience (Björnsdotter and Olausson, 2011;Francis et al, 1999;McGlone et al, 2014;Olausson et al, 2002;Olausson et al, 2010;Perini and Olausson, 2015). The pleasantness of CT-optimal touch has been proposed to be related to increased levels of serotonin and oxytocin (Trotter et al, 2016;Uvnäs-Moberg, 1998;Walker and McGlone, 2013;Walker and McGlone, 2017a), both of which are influenced by MDMA. Interestingly, recreational MDMA users report that MDMA increases the pleasantness of social touch (Klein et al, 2009).…”
Section: Introductionmentioning
confidence: 99%